Occupational risk factors for female breast cancer: a review. Issue 3 (March 1996) - Goldberg, M S; Labrèche, F
Abstract : OBJECTIVES: Although progress has been made in identifying personal risk factors and in improving treatment for female breast cancer, incidence rates continue to increase. With women now occupying a sizable fraction of the workforce, it is worth inquiring whether there are occupational risk factors for breast cancer. This is a review of occupational studies on female breast cancer. METHODS: Suitable reports and published articles with associations of female breast cancer and occupation were identified from technical reports, by searching the MEDLINE bibliographic data base, and by reviewing each paper on cancer that was published in 20 major journals during the period from about 1971-94. RESULTS: A total of 115 studies were identified; 19 studies relied exclusively on data collected for administrative purposes, and there were four incident case-control studies and 92 cohort studies. Although data for individual industries, occupations, and exposures were sparse, there was limited evidence of an association with employment in the pharmaceutical industry and among cosmetologists and beauticians. Associations were also found for chemists and occupations with possible exposure to extremely low frequency electromagnetic fields, but potential methodological weaknesses preclude drawing any definite conclusions. There was little support for increased risks among textiles workers, dry cleaning workers, and nuclear industry workers. CONCLUSIONS: Few high quality occupational studies directed specifically toward women have been carried out to allow the unambiguous identification of occupational risk factors for breast cancer. It is suggested that investigations that account for non-occupational risk factors and that assess exposure in a more detailed way be carried out. One strategy already suggested is to conduct population based, case-control studies in which subjects are interviewed about their occupational histories and exposure to chemical and physical agents which are then attributed from the job descriptions by a team of experts. These studies can then be supplemented when necessary with cohort studies of specific populations.